2008
DOI: 10.1111/j.1365-246x.2008.03755.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth extent of the fault-zone seismic waveguide: effects of increasing velocity with depth

Abstract: S U M M A R YThe damage zone of a major fault can act as a low-velocity seismic waveguide. The fault-zone guided waves provide a potential method to constrain the in situ physical properties of the fault zone (FZ) at depth. Recently, there has been debate over the depth extent of observed fault waveguides and whether fault properties at seismogenic depth can be constrained by guided waves (GWs). To address these questions, elastic finite-difference synthetic seismograms were generated for fault-zone models tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 33 publications
(91 reference statements)
1
28
0
Order By: Relevance
“…Ben‐Zion et al 2003; Peng et al 2003; Lewis et al 2005). A recent numerical analysis of FZ trapped wave pointed out that determination of fault structure at seismogenic depth requires analysis of data at higher frequencies than the FZ trapped wave (Wu et al 2008). In this study, we used precursors before the direct S waves, the S diff waves, which are sensitive to LVZ depth (Li et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ben‐Zion et al 2003; Peng et al 2003; Lewis et al 2005). A recent numerical analysis of FZ trapped wave pointed out that determination of fault structure at seismogenic depth requires analysis of data at higher frequencies than the FZ trapped wave (Wu et al 2008). In this study, we used precursors before the direct S waves, the S diff waves, which are sensitive to LVZ depth (Li et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Guided waves are hardly distinct for sources below the subducted crust. Li & Vidale (1996), Ben‐Zion (1998), Jahnke et al (2002), Igel et al (2002a), Fohrmann et al (2004) and Wu et al (2008) modelled wave propagation for sources outside a fault zone to investigate, if trapped waves can also be generated by energy transmission into the LVL. They conclude that amplitudes of guided waves are weaker or hardly generated, if sources are located beside a LVL that is continuous with depth.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, seismic wave energy can also be recorded on top of the adjacent layers at any distance to the waveguide (Li & Vidale 1996; Igel et al 1997) and sources beside the LVL produce stronger guided waves by energy transmission into the waveguide (Igel et al 1997). Wu et al (2008) demonstrated that the trapping efficiency of a waveguide changes, if increasing velocities with depth both inside and outside the structure are considered.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than relating d to a cutoff in surface roughness, we identify it as the half width of a volumetric “damage zone,” where small‐scale stress heterogeneity is attenuated by low rock strength (Figure 16). Damage zones with dimensions of tens to hundreds of meters are widely recognized features of exhumed strike‐slip faults [ Chester and Logan , 1986; Chester et al , 1993; Ben‐Zion and Sammis , 2003; Chester et al , 2005; Rockwell and Ben‐Zion , 2007], and they have been used to explain vertical low‐velocity zones of comparable dimensions inferred from fault zone guided waves [ Li et al , 1990]; these low‐velocity zones extend at least to several kilometers [ Ben‐Zion et al , 2003; Peng et al , 2003; Lewis et al , 2005] and perhaps deeper [ Li et al , 2004; Wu et al , 2008]. Drill samples across the Nojima fault, which ruptured in the 1995 Kobe earthquake, indicate that shear strength is significantly reduced and the permeability increased within a damage zone surrounding the fault core [ Lockner et al , 1999].…”
Section: Rough Fault Loading Modelmentioning
confidence: 99%